Implementación de un sistema contable de costos de producción a la industria en acero y cerrajería metalmecánica e.q en el periodo bimestral del 1 de julio al 31 de agosto del 2013 - Catota Zapata, Carmen Patricia (2016)
This research work is aimed at reviewing and evaluating whether the methods, systems and procedures are followed at all stages of the production process ensures compliance with policies, plans, programs, and regulations that may have a significant impact on their activities. In the first chapter a search for topics related to research, besides reading of official documents and bibliographic administrative character on theoretical grounds, with the idea of clarifying some concepts for each topic definition proposed is conducted. In chapter two different techniques were combined as reviewing books and the Internet, as required for this research, including reading secondary sources, observation, key informant interviews Industry. The proposal is oriented to the implementation of a cost system, based on the principles t accounting methods under rules and regulations described in the third chapter; for that reason begins by identifying the main problem and then quickly and specifically, The designed system is an instrument adequately control aimed at the institution, for correct operation of the production department and allow make timely and reliable decisions.